What Is the Role of Religious Commitment between an Extrovert Personality and Moral Disengagement through Prosocial/Antisocial Behaviours and Moral Identity? An Investigation on Student-Athletes - TOGO, OSMAN TOLGA; BOZDOĞAN, TUBA (My University, 2024)
Moral disengagement in sports refers to the psychological process through which individuals distance themselves from the ethical implications of their actions within the sporting context. This study aims to examine the role of religious commitment between personality traits and moral disengagement and investigate the role of prosocial and antisocial behaviours and moral identity. Student-athletes were recruited from individual and team sports, including football, basketball, handball, volleyball, wrestling, combat sports, swimming, track and field, cycling, badminton, and futsal. We hypothesised that extrovert personality traits directly predict moral identity, religious commitment, and prosocial/antisocial behaviours. Extraversion predicted moral disengagement with the mediation roles of internalisation, symbolisation, religious commitment, and pro- and antisocial behaviours. Our findings provide insights into the complex relationships between personality traits, internalisation, symbolisation, religious commitment, social behaviours, and their impact on moral disengagement. They highlight the importance of considering internalisation, symbolisation, and religious commitment mediating roles in understanding the relationships between extraversion, social behaviours, and moral disengagement. Understanding the complex relationship among these factors can inform the development of tailored interventions that address individual athletes’ needs and characteristics. Our study contributes to the growing body of literature on the psychological underpinnings of ethical behaviour in sports. By elucidating the roles of extraversion, moral identity, religious commitment, and social behaviours in moral disengagement, this research provides a more nuanced understanding of the factors influencing ethical decision-making and behaviour in student-athletes. Keywords: student-athletes; religious commitment; moral behaviours
Keywords: Sosyal ve Beşeri Bilimler; İlahiyat; Social Sciences and Humanities; Theology; Sanat ve Beşeri Bilimler (AHCI); Sanat ve Beşeri Bilimler; DİN; Arts & Humanities (AHCI); ARTS & HUMANITIES; RELIGION; Dini çalışmalar; Sosyal Bilimler ve Beşeri Bilimler; Religious Studies; Social Sciences & Humanities; moral behaviours; religious commitment; student-athletes